2022
DOI: 10.5858/arpa.2021-0165-ra
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B-Cell Lymphoma

Abstract: Context.— Intravascular large B-cell lymphoma (IVLBCL) is a rare hematopathologic entity, posing both a clinical and histologic challenge for diagnosis. Numerous pitfalls can hinder making the diagnosis. Objective.— To summarize recent developments in literature pertaining to IVLBCL and point out key pitfalls pathologists should be prepared to encounter. Data Sources.— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…The role of bone marrow and skin biopsies in IVLBCL diagnosis is critical, as highlighted by previous articles, which emphasized that IVLBCL can present with various nonspecific symptoms, including fever of unknown origin. That biopsy of involved tissues often provides a definitive diagnosis [ 20 ]. However, in our case, the biopsy of the bone marrow could be performed because of the critical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The role of bone marrow and skin biopsies in IVLBCL diagnosis is critical, as highlighted by previous articles, which emphasized that IVLBCL can present with various nonspecific symptoms, including fever of unknown origin. That biopsy of involved tissues often provides a definitive diagnosis [ 20 ]. However, in our case, the biopsy of the bone marrow could be performed because of the critical condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…IVLBCL commonly affects the skin and central nervous system, and symptoms at presentation are based on the site of involvement. Approximately 55% and 76% of patients present with some B symptoms, especially a fever ( 2 ), and a Japanese single-center retrospective study found a persistent fever in 97.6% of patients ( 8 ). In contrast, when diagnosed incidentally, as in our case, patients may have no overt symptoms ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of extranodal large B-cell lymphoma characterized by the selective proliferation of lymphoma cells within the lumen of small blood vessels in various organs ( 1 ). IVLBCL commonly involves the skin and central nervous system (CNS), and approximately 55-76% of patients present with some B symptoms, especially a fever ( 2 ). Although autopsy findings revealed that intravascular lymphoma often involves the lungs, early presentation of the lungs has rarely been reported because of diagnostic difficulties ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cases with brain or CSF infiltration by lymphoma cells, methotrexate may be added to cross the blood brain barrier (BBB) [4] . Intrathecal therapy particularly in cases with CNS involvement is poorly understood, however high dose methotrexate with intrathecal chemotherapy appears to be effective in patients without this factor [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%